Modified glass fiber reinforced polyamide composite material and preparation method thereof
By grafting graphene oxide and nanotitanium dioxide on the surface of the glass fiber to form a dense physical barrier layer and a radical capture layer, the problems of 'wick effect' and mechanical performance degradation in glass fiber reinforced polyamide materials are solved, and efficient flame retardant performance and mechanical performance balance is achieved.
Patent Information
- Application Number
- CN202411914515.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-24
AI Technical Summary
In the prior art, flame retardants cannot effectively solve the ‘wick effect’ caused by glass fiber (GF), resulting in poor flame retardant performance of glass fiber reinforced polyamide materials (GF/PA), and the addition of flame retardants also leads to a decline in the mechanical properties of the material.
Graphene oxide modified glass fiber is combined with halogen-free flame retardant. By grafting graphene oxide and nanotitanium dioxide on the surface of the glass fiber, a dense physical barrier layer and a free radical capture layer are formed to jointly improve the flame retardant performance of the material.
It effectively eliminates the 'wick effect' of GF/PA material when burning, improves the flame retardant performance of the material, and maintains excellent mechanical properties, meeting the application needs of high fire resistance requirements.
Smart Images

Figure BDA0005206523830000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and particularly relates to a modified glass fiber reinforced polyamide composite material and a preparation method thereof. Background Art
[0002] Glass fiber (GF) reinforced polyamide resin (PA) composite materials (GF / PA materials) have excellent mechanical strength, good thermal stability and wear resistance, and are widely used in the automotive industry, aerospace, electronic products, sports equipment and other fields. As the requirements for material safety in terminal applications continue to increase, GF / PA materials must have good flame retardant properties to reduce the risk of fire. For GF / PA materials, on the one hand, PA, as an organic polymer material, contains a large amount of carbon and hydrogen elements, which will release flammable gases at high temperatures and easily react with oxygen to cause combustion. In addition, PA will also produce a large number of molten droplets when burning, exacerbating the fire. On the other hand, although GF itself is non-flammable, the introduction of GF will produce a "wick effect", which will intensify its combustion process. Therefore, the development of effective flame retardant technology to improve the flame retardant properties of GF / PA materials has always been an urgent and important research direction for industry and academia.
[0003] At present, the industry generally improves the flame retardancy of GF / PA materials by adding flame retardants. Conventional flame retardants achieve flame retardancy through physical effects, such as dehydration and heat absorption to reduce the temperature of the burning surface of the material, preventing oxygen from entering the material to continue to participate in the combustion reaction; on the other hand, they achieve flame retardancy through chemical effects such as capturing free radicals and promoting carbonization. However, this traditional flame retardant method cannot solve the "wick effect" caused by GF, and the added flame retardant will also seriously affect the mechanical properties of GF / PA materials, so it cannot meet the application needs in fields with higher fire protection requirements.
[0004] In recent years, new progress has been made in the research on solving the GF "wick effect" through GF surface modification technology. A preparation process of glass fiber composite material reinforced modified PET material is disclosed in the Chinese patent with patent number CN202410466322.9. The patent is to graft the nitrogen-phosphorus flame-retardant polymer of cyclotriphosphazene and carbazole to the surface of glass fiber to form a glass fiber composite flame retardant. Because the nitrogen-phosphorus flame-retardant polymer contains more aromatic ring structures, a continuous and dense carbon layer can be formed on the surface of the glass fiber, and a composite carbon-glass fiber barrier layer can be formed with the glass fiber, which plays a role in heat insulation, isolation of oxygen, and prevention of molten droplets, thereby achieving a synergistic flame retardant effect. However, this flame retardant method of modifying glass fiber with flame retardant will reduce the surface energy of glass fiber, and the reduction of surface energy will lead to poor compatibility between glass fiber and polymer resin interface, resulting in poor mechanical properties of the composite material, and the effect of balancing flame retardant and mechanical properties cannot be achieved. Summary of the invention
[0005] The present invention aims to solve the technical problems that the flame retardant in the prior art cannot effectively solve the "wick effect" caused by GF, thereby resulting in poor flame retardancy of GF / PA materials, and the addition of the flame retardant causes the mechanical properties of the GF / PA materials to decrease. A modified glass fiber reinforced polyamide composite material and a preparation method thereof are proposed to effectively solve the "wick effect" caused by GF, thereby improving the flame retardancy of the GF / PA materials, and at the same time effectively maintaining the mechanical properties of the GF / PA materials from being reduced.
[0006] In order to achieve the above object, the present invention adopts the following technical scheme:
[0007] A modified glass fiber reinforced polyamide composite material, wherein the raw materials thereof include the following components in parts by weight:
[0008] Graphene oxide modified glass fiber: 10-40 parts by weight,
[0009] Polyamide resin: 44-83 parts by weight,
[0010] Flame retardant: 5-12 parts by weight,
[0011] Lubricant: 0.2-0.5 parts by weight,
[0012] Additives: 1-3 parts by weight.
[0013] Furthermore, the method for preparing the graphene oxide modified glass fiber comprises the following steps:
[0014] S1, adding glass fiber to Tris-HCl buffer, and dispersing by ultrasonic for 15-25 minutes to obtain a mixed dispersion; wherein the addition ratio of the glass fiber to the Tris-HCl buffer is 10g:1000mL; the concentration of the Tris-HCl buffer is 0.01mol / L, and the pH is 8.5;
[0015] S2, adding dopamine hydrochloride to the mixed dispersion and stirring continuously at room temperature for more than 18 hours, when the mixed dispersion changes from yellow-brown to black, the reaction is completed and the stirring is stopped, the mixed dispersion is centrifuged, and the centrifuged product is repeatedly washed with ethanol and deionized water to obtain polydopamine coated glass fiber; wherein the addition ratio of the dopamine hydrochloride to the glass fiber is 1g:10g;
[0016] S3. Add polydopamine coated glass fiber, dopamine hydrochloride, nano titanium dioxide and graphene oxide in Tris-HCl buffer in sequence, and stir continuously at room temperature for more than 18 hours, then centrifuge, wash the centrifugal product repeatedly with ethanol and deionized water, and vacuum dry at 80°C to constant weight to obtain the graphene oxide modified glass fiber; wherein, in this step, the addition ratio of the Tris-HCl buffer, polydopamine coated glass fiber, dopamine hydrochloride, nano titanium dioxide and graphene oxide is 1000mL: 10g: 0.5g: 0.5g: 2g; the concentration of the Tris-HCl buffer is 0.01mol / L, and the pH is 8.5.
[0017] Furthermore, the glass fiber is an alkali-free chopped glass fiber, the glass fiber diameter is ≤15 μm, and the glass fiber chopped length is ≤5 mm.
[0018] Furthermore, the polyamide resin is at least one of PA6, PA66, PA56, PA610, PA612, PA11, PA12, PA1010, and PA1012; and the relative viscosity of the polyamide resin is ≥2.0dl / g.
[0019] Furthermore, the flame retardant is a halogen-free flame retardant, preferably at least one of red phosphorus flame retardant (RP), aluminum diethylphosphinate flame retardant (ADP), melamine polyphosphate (MPP), and melamine cyanurate (MCA).
[0020] Furthermore, the lubricant is one of modified ethylene bis fatty acid amide (TAF for short), silicone masterbatch, montan wax, or a mixture of any two or more thereof in any ratio.
[0021] Furthermore, the silicone masterbatch contains more than 50% ultra-high molecular weight siloxane, and the remaining carrier resin is LDPE or PA6; the montan wax is a mixture of OP wax and E wax; and the addition ratio of OP wax to E wax in the mixture of OP wax and E wax is 2:1.
[0022] Furthermore, the auxiliary agent is at least one of an antioxidant, a photoaging auxiliary agent, and a colorant.
[0023] The antioxidant is a mixture of a hindered phenol antioxidant and a phosphite antioxidant; the hindered phenol antioxidant is antioxidant 1098; the phosphite antioxidant is antioxidant 168; the ratio of the added amount of antioxidant 1098 to antioxidant 168 in the mixture of the hindered phenol antioxidant and the phosphite antioxidant is 1:1;
[0024] The light aging agent is a mixture of an ultraviolet absorber and a light stabilizer; the ultraviolet absorber is UV-234; the light stabilizer is UV-944; the addition ratio of UV-234 to UV-944 in the mixture of the ultraviolet absorber and the light stabilizer is 1:1.
[0025] A method for preparing the modified glass fiber reinforced polyamide composite material as described above comprises the following steps:
[0026] The polyamide resin, flame retardant, lubricant and additives are mixed evenly and added to the main feeding port of the twin-screw extruder, and the graphene oxide modified glass fiber is added to the side feeding port of the twin-screw extruder according to the weight ratio. The composite material is obtained by melt blending, extruding and granulating through the twin-screw extruder.
[0027] The beneficial effects of the present invention are:
[0028] The present application adopts graphene oxide modified glass fiber, and the mode of compounding with halogen-free flame retardant can not only effectively improve the flame retardant properties of GF / PA materials, but also ensure that it has excellent mechanical properties. Among them, the active functional groups of graphene oxide grafted on the surface of glass fiber can interact with the polyamide resin matrix, enhance the interfacial bonding force between glass fiber and polyamide resin matrix, and then effectively improve the mechanical properties of glass fiber and polyamide resin compound matrix. At the same time, the graphene oxide with unique lamellar structure is evenly dispersed in the polyamide resin and superimposed layer by layer to form a dense physical barrier layer, blocking the flow of polyamide melt along the glass fiber, and then eliminating the "candle wick effect" caused by GF when GF / PA material burns, thereby avoiding the occurrence of aggravated fire. In addition, graphene oxide modified glass fiber also has certain free radical capture and carbonization capabilities, and it is compounded with halogen-free flame retardant to play a synergistic flame retardant role, which is conducive to further improving the flame retardancy of the material.
[0029] In the preparation of graphene oxide modified glass fiber, the present application preferentially places the glass fiber in Tris-HCl buffer for uniform dispersion, and then stirs together for more than 18 hours after adding dopamine hydrochloride, so that dopamine can form a polydopamine layer with strong adsorption capacity on the surface of the glass fiber, thereby effectively ensuring that graphene oxide can be uniformly adhered to the surface of the glass fiber. Polydopamine interacts with the active functional groups on the surface of graphene oxide, so that graphene oxide is reduced and peeled off, and anchored between its sheet structures, increasing the specific surface area, which is conducive to the polyamide resin to wrap the graphene oxide sheet, and improving the dispersibility of graphene oxide in polyamide resin. In addition, the present application sets the addition ratio of polydopamine coated glass fiber to graphene oxide to 10:2, which can effectively ensure that the surface of the chopped glass fiber can be uniformly coated with graphene oxide. Among them, if the addition amount of graphene oxide is too low, a complete coating cannot be formed on the surface of the glass fiber, and if the addition amount of graphene oxide is too high, self-polymerization will occur, resulting in uneven coating and agglomeration on the surface of the glass fiber. At the same time, nano-titanium dioxide particles are deposited on the surface of graphene oxide. The presence of nano-particles can not only prevent the agglomeration of graphene oxide nanosheets, but also block the gap between glass fiber and polyamide resin, which is more conducive to the combination of glass fiber and polyamide resin.
[0030] The modified glass fiber reinforced polyamide composite material prepared in the present application can be used in the automotive industry, such as key components such as engine hoods, body frames, and door interior panels, and has broad application prospects. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present application will be clearly and completely described below in combination with the technical scheme of the embodiment. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application. In the description of the present application, the experimental methods, unless otherwise specified, are conventional methods; the reagents and materials, unless otherwise specified, can be obtained from commercial channels.
[0032] The disclosure below provides many different embodiments or examples to implement the present application. In order to simplify the disclosure of the present application, the components and settings of specific examples are described below. Of course, they are only examples, and the purpose is not to limit the present application. Those of ordinary skill in the art can appreciate the application of other processes and / or the use of other materials.
[0033] The sources of the main raw materials in the following embodiments and comparative examples of the present invention are as follows:
[0034] The glass fiber grade was ECS-10-3.0-T435TM, with a fiber diameter of 10 μm and a short cut length of 3.0 mm, purchased from Taishan Glass Fiber Co., Ltd.
[0035] Graphene oxide, diameter 0.5-3 μm, thickness 0.55-1.20 nm, purity > 99%, purchased from Beijing Dekedaojin Technology Co., Ltd.;
[0036] Dopamine hydrochloride, CAS registration number: 62-31-7, molecular formula: C8H11NO2·HCl, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0037] Tris-HCl buffer, 1 M, pH 8.5, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0038] Nano titanium dioxide, CAS registration number: 13463-67-7, particle size 5-20nm, purity >99.8%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0039] The polyamide 6 (PA6) resin was HY-2800 with a relative viscosity of 2.8 dl / g and was purchased from Haiyang Technology Co., Ltd.;
[0040] The polyamide 66 (PA66) resin was EPR24 with a relative viscosity of 2.4 dl / g and was purchased from Shenma Industrial Co., Ltd.
[0041] The red phosphorus flame retardant is FRP-950-1, with a microencapsulated red phosphorus content of ≥70%, purchased from Guangzhou Yinsu Flame Retardant New Materials Co., Ltd.
[0042] The aluminum diethylphosphinate flame retardant is ADP-33 with a phosphorus content of 23.3-24%, purchased from Qingdao Oupure New Materials Co., Ltd.
[0043] The silicone masterbatch was GT-500, the carrier resin was LLDPE, and the content of ultra-high molecular weight siloxane was 60%, purchased from Zhejiang Jiahua Fine Chemical Co., Ltd.
[0044] The OP wax brand is LicowaxOP, purchased from Clariant;
[0045] The brand of E wax is LicowaxE, purchased from Clariant;
[0046] The brand of antioxidant 1098 is Irganox 1098, CAS registration number: 23128-74-7, purchased from BASF;
[0047] The brand of antioxidant 168 is Irganox 168, CAS registration number: 31570-04-4, purchased from BASF;
[0048] The brand of ultraviolet absorber UV-234 is Tinuvn 234, CAS registration number: 70321-86-7, purchased from BASF;
[0049] The light stabilizer UV-944 is Chimassorb 944, CAS registration number: 71878-19-8, purchased from BASF;
[0050] The remaining reagents were commercially available products.
[0051] The detection methods used in the performance detection of the corresponding products in the embodiments and comparative examples of the present invention are as follows:
[0052] The glass fiber reinforced polyamide composite material is placed in an injection molding machine to make a standard sample, and then the performance test is carried out. Among them, the injection molding temperature of polyamide 6 (PA6) is 250-275℃, and the injection molding temperature of polyamide 66 (PA66) is 270-300℃.
[0053] The tensile strength was determined according to ISO 527 method, with a gauge length of 75 mm and a test speed of 5 mm / min;
[0054] The flexural strength was determined according to ISO 178 method, with a span of 64 mm and a test speed of 2 mm / min;
[0055] The notched impact strength of the simply supported beam was determined according to ISO 179 method, with a pendulum energy of 4J;
[0056] The vertical burning performance is measured according to UL94 standard, 20mm flame, sample size 125mm×12mm×0.8mm.
[0057] Example 1
[0058] A method for preparing a modified glass fiber reinforced polyamide composite material comprises the following steps:
[0059] 580g PA6 resin, 70g red phosphorus flame retardant, 30g diethyl phosphinate aluminum flame retardant, 2g lubricant and 18g additive were mixed evenly and added to the main feeding port of the twin-screw extruder, and then 300g graphene oxide modified glass fiber was added to the side feeding port of the twin-screw extruder. After melt blending, extrusion and granulation in the twin-screw extruder, the modified glass fiber reinforced polyamide composite material was obtained, which was recorded as S1.
[0060] Wherein, the preparation method of the graphene oxide modified chopped glass fiber is as follows:
[0061] S1, adding 100g of glass fiber into 10L of Tris-HCl buffer, and dispersing by ultrasonic for 20 minutes to obtain a mixed dispersion; wherein the concentration of the Tris-HCl buffer is 0.01mol / L, and the pH is 8.5;
[0062] S2, adding 10g of dopamine hydrochloride to the mixed dispersion obtained in step S1 and stirring continuously at room temperature for more than 18 hours, when the mixed dispersion changes from yellow-brown to black, the reaction is completed and the stirring is stopped, the mixed dispersion is centrifuged, and the centrifuged product is repeatedly washed with ethanol and deionized water to obtain a polydopamine coated glass fiber;
[0063] S3. Add the polydopamine coated glass fiber obtained in step S2, 5 g of dopamine hydrochloride, 5 g of nano-titanium dioxide, and 20 g of graphene oxide to 10 L of Tris-HCl buffer in sequence, and stir continuously at room temperature for 24 hours, then centrifuge, wash the centrifugal product repeatedly with ethanol and deionized water, and vacuum dry at 80° C. to constant weight to obtain the graphene oxide modified glass fiber; wherein the concentration of the Tris-HCl buffer is 0.01 mol / L, and the pH is 8.5.
[0064] The lubricant is silicone masterbatch, the auxiliary agent is an antioxidant, and the antioxidant is a mixture of hindered phenol antioxidants and phosphite antioxidants; the hindered phenol antioxidant is antioxidant 1098; the phosphite antioxidant is antioxidant 168; the mass ratio of antioxidant 1098 to antioxidant 168 in the mixture of hindered phenol antioxidants and phosphite antioxidants is 1:1.
[0065] Example 2
[0066] A method for preparing a modified glass fiber reinforced polyamide composite material comprises the following steps:
[0067] 660g PA6 resin, 90g red phosphorus flame retardant, 30g diethyl aluminum phosphite flame retardant, 2g lubricant and 18g additive were mixed evenly and added to the main feeding port of the twin-screw extruder, and then 200g graphene oxide modified glass fiber was added to the side feeding port of the twin-screw extruder. After melt blending, extrusion and granulation in the twin-screw extruder, the modified glass fiber reinforced polyamide composite material was obtained, which was recorded as S2.
[0068] In this embodiment, the preparation method of the graphene oxide modified chopped glass fibers, the type of the lubricant and the type of the auxiliary agent are consistent with those in Example 1.
[0069] Example 3
[0070] A method for preparing a modified glass fiber reinforced polyamide composite material comprises the following steps:
[0071] 800g PA66 resin, 30g red phosphorus flame retardant, 40g diethyl aluminum phosphite flame retardant, 5g lubricant and 25g additive were mixed evenly and added to the main feeding port of the twin-screw extruder, and then 100g graphene oxide modified glass fiber was added to the side feeding port of the twin-screw extruder. After melt blending, extrusion and granulation in the twin-screw extruder, the modified glass fiber reinforced polyamide composite material was obtained, which was recorded as S3.
[0072] In this embodiment, the preparation method of the graphene oxide modified chopped glass fibers is consistent with that in Embodiment 1.
[0073] The lubricant is a mixture of OP wax and E wax in a mass ratio of 2:1;
[0074] The auxiliary agent is a photoaging agent, which is a mixture of an ultraviolet light absorber and a light stabilizer; the ultraviolet light absorber is UV-234; the light stabilizer is UV-944; the mass ratio of UV-234 to UV-944 in the mixture of the ultraviolet light absorber and the light stabilizer is 1:1.
[0075] Comparative Example 1
[0076] A method for preparing a glass fiber reinforced polyamide composite material comprises the following steps:
[0077] 580g PA6 resin, 70g red phosphorus flame retardant, 30g diethyl phosphinate aluminum flame retardant, 2g lubricant and 18g additive were mixed evenly and added to the main feeding port of the twin-screw extruder, and then 300g chopped glass fiber was added to the side feeding port of the twin-screw extruder. After melt blending, extrusion and granulation in the twin-screw extruder, the glass fiber reinforced polyamide composite material was obtained, which was recorded as D1.
[0078] The lubricant is silicone masterbatch, the auxiliary agent is an antioxidant, and the antioxidant is a mixture of hindered phenol antioxidants and phosphite antioxidants; the hindered phenol antioxidant is antioxidant 1098; the phosphite antioxidant is antioxidant 168; the mass ratio of antioxidant 1098 to antioxidant 168 in the mixture of hindered phenol antioxidants and phosphite antioxidants is 1:1.
[0079] The difference between this comparative example and the above-mentioned Example 1 is that the graphene oxide-modified chopped glass fibers are replaced with unmodified chopped glass fibers.
[0080] Comparative Example 2
[0081] A method for preparing a modified glass fiber reinforced polyamide composite material comprises the following steps:
[0082] 580g PA6 resin, 70g red phosphorus flame retardant, 30g diethyl aluminum phosphite flame retardant, 2g lubricant and 18g additive were mixed evenly and added to the main feeding port of the twin-screw extruder, and then 300g graphene oxide modified glass fiber was added to the side feeding port of the twin-screw extruder. After melt blending, extrusion and granulation in the twin-screw extruder, the modified glass fiber reinforced polyamide composite material was obtained, which was recorded as D2.
[0083] Wherein, the preparation method of the graphene oxide modified chopped glass fiber is as follows:
[0084] S1, adding 100g of glass fiber into 10L of Tris-HCl buffer, and dispersing by ultrasonic for 20 minutes to obtain a mixed dispersion; wherein the concentration of the Tris-HCl buffer is 0.01mol / L, and the pH is 8.5;
[0085] S2, adding 10g of dopamine hydrochloride to the mixed dispersion obtained in step S1 and stirring continuously at room temperature for more than 18 hours, when the mixed dispersion changes from yellow-brown to black, the reaction is completed and the stirring is stopped, the mixed dispersion is centrifuged, and the centrifuged product is repeatedly washed with ethanol and deionized water to obtain a polydopamine coated glass fiber;
[0086] S3. Add the polydopamine coated glass fiber obtained in step S2, 5 g of dopamine hydrochloride, 5 g of nano-titanium dioxide, and 10 g of graphene oxide to 10 L of Tris-HCl buffer in sequence, and stir continuously at room temperature for 24 hours, then centrifuge, wash the centrifugal product repeatedly with ethanol and deionized water, and vacuum dry at 80° C. to constant weight to obtain the graphene oxide modified glass fiber; wherein the concentration of the Tris-HCl buffer is 0.01 mol / L, and the pH is 8.5.
[0087] The lubricant is silicone masterbatch, the auxiliary agent is an antioxidant, and the antioxidant is a mixture of hindered phenol antioxidants and phosphite antioxidants; the hindered phenol antioxidant is antioxidant 1098; the phosphite antioxidant is antioxidant 168; the mass ratio of antioxidant 1098 to antioxidant 168 in the mixture of hindered phenol antioxidants and phosphite antioxidants is 1:1.
[0088] The difference between this comparative example and the above-mentioned Example 1 is that the amount of graphene oxide used is reduced from 20 g to 10 g when preparing graphene oxide-modified chopped glass fibers.
[0089] Comparative Example 3
[0090] A method for preparing a modified glass fiber reinforced polyamide composite material comprises the following steps:
[0091] 580g PA6 resin, 70g red phosphorus flame retardant, 30g diethyl phosphinate aluminum flame retardant, 2g lubricant and 18g additive were mixed evenly and added to the main feeding port of the twin-screw extruder, and then 300g graphene oxide modified glass fiber was added to the side feeding port of the twin-screw extruder. After melt blending, extrusion and granulation in the twin-screw extruder, the modified glass fiber reinforced polyamide composite material was obtained, which was recorded as D3.
[0092] Wherein, the preparation method of the graphene oxide modified chopped glass fiber is as follows:
[0093] S1, adding 100g of glass fiber into 10L of Tris-HCl buffer, and dispersing by ultrasonic for 20 minutes to obtain a mixed dispersion; wherein the concentration of the Tris-HCl buffer is 0.01mol / L, and the pH is 8.5;
[0094] S2, adding 10g of dopamine hydrochloride to the mixed dispersion obtained in step S1 and stirring continuously at room temperature for more than 18 hours, when the mixed dispersion changes from yellow-brown to black, the reaction is completed and the stirring is stopped, the mixed dispersion is centrifuged, and the centrifuged product is repeatedly washed with ethanol and deionized water to obtain a polydopamine coated glass fiber;
[0095] S3. Add the polydopamine coated glass fiber obtained in step S2, 5 g of dopamine hydrochloride, 5 g of nano-titanium dioxide, and 30 g of graphene oxide to 10 L of Tris-HCl buffer in sequence, and stir continuously at room temperature for 24 hours, then centrifuge, wash the centrifugal product repeatedly with ethanol and deionized water, and vacuum dry at 80°C to constant weight to obtain the graphene oxide modified glass fiber; wherein the concentration of the Tris-HCl buffer is 0.01 mol / L, and the pH is 8.5.
[0096] The lubricant is silicone masterbatch, the auxiliary agent is an antioxidant, and the antioxidant is a mixture of hindered phenol antioxidants and phosphite antioxidants; the hindered phenol antioxidant is antioxidant 1098; the phosphite antioxidant is antioxidant 168; the mass ratio of antioxidant 1098 to antioxidant 168 in the mixture of hindered phenol antioxidants and phosphite antioxidants is 1:1.
[0097] The difference between this comparative example and the above-mentioned Example 1 is that the amount of graphene oxide is increased from 20 g to 30 g when preparing graphene oxide-modified chopped glass fibers.
[0098] Comparative Example 4
[0099] A method for preparing a modified glass fiber reinforced polyamide composite material comprises the following steps:
[0100] 580g PA6 resin, 70g red phosphorus flame retardant, 30g diethyl phosphinate aluminum flame retardant, 2g lubricant and 18g additive were mixed evenly and added to the main feeding port of the twin-screw extruder, and then 300g graphene oxide modified glass fiber was added to the side feeding port of the twin-screw extruder. After melt blending, extrusion and granulation in the twin-screw extruder, the modified glass fiber reinforced polyamide composite material was obtained, which was recorded as D4.
[0101] Wherein, the preparation method of the graphene oxide modified chopped glass fiber is as follows:
[0102] S1, adding 100g of glass fiber into 10L of Tris-HCl buffer, and dispersing by ultrasonic for 20 minutes to obtain a mixed dispersion; wherein the concentration of the Tris-HCl buffer is 0.01mol / L, and the pH is 8.5;
[0103] S2, adding 10g of dopamine hydrochloride to the mixed dispersion obtained in step S1 and stirring continuously at room temperature for more than 18 hours, when the mixed dispersion changes from yellow-brown to black, the reaction is completed and the stirring is stopped, the mixed dispersion is centrifuged, and the centrifuged product is repeatedly washed with ethanol and deionized water to obtain a polydopamine coated glass fiber;
[0104] S3. Add the polydopamine coated glass fiber obtained in step S2, 10 g of dopamine hydrochloride, and 20 g of graphene oxide to 10 L of Tris-HCl buffer in sequence, and stir continuously at room temperature for 24 hours, then centrifuge, wash the centrifugal product repeatedly with ethanol and deionized water, and vacuum dry at 80° C. to constant weight to obtain the graphene oxide modified glass fiber; wherein the concentration of the Tris-HCl buffer is 0.01 mol / L, and the pH is 8.5.
[0105] The lubricant is silicone masterbatch, the auxiliary agent is an antioxidant, and the antioxidant is a mixture of hindered phenol antioxidants and phosphite antioxidants; the hindered phenol antioxidant is antioxidant 1098; the phosphite antioxidant is antioxidant 168; the mass ratio of antioxidant 1098 to antioxidant 168 in the mixture of hindered phenol antioxidants and phosphite antioxidants is 1:1.
[0106] The difference between this comparative example and the above-mentioned Example 1 is that nano-titanium dioxide is replaced with dopamine hydrochloride when preparing graphene oxide-modified chopped glass fibers.
[0107] Comparative Example 5
[0108] A method for preparing a modified glass fiber reinforced polyamide composite material comprises the following steps:
[0109] 580g PA6 resin, 70g red phosphorus flame retardant, 30g diethyl phosphinate aluminum flame retardant, 2g lubricant and 18g additive were mixed evenly and added to the main feeding port of the twin-screw extruder, and then 300g graphene oxide modified glass fiber was added to the side feeding port of the twin-screw extruder. After melt blending, extrusion and granulation in the twin-screw extruder, the modified glass fiber reinforced polyamide composite material was obtained, which was recorded as D5.
[0110] Wherein, the preparation method of the graphene oxide modified chopped glass fiber is as follows:
[0111] 100 g of glass fiber, 5 g of dopamine hydrochloride, 5 g of nano-titanium dioxide, and 20 g of graphene oxide are added to 10 L of Tris-HCl buffer in sequence, and stirred continuously at room temperature for 24 hours, and then centrifuged. The centrifuged product is repeatedly washed with ethanol and deionized water, and vacuum dried at 80° C. to constant weight to obtain the graphene oxide-modified glass fiber; wherein the concentration of the Tris-HCl buffer is 0.01 mol / L, and the pH is 8.5.
[0112] The lubricant is silicone masterbatch, the auxiliary agent is an antioxidant, and the antioxidant is a mixture of hindered phenol antioxidants and phosphite antioxidants; the hindered phenol antioxidant is antioxidant 1098; the phosphite antioxidant is antioxidant 168; the mass ratio of antioxidant 1098 to antioxidant 168 in the mixture of hindered phenol antioxidants and phosphite antioxidants is 1:1.
[0113] The difference between this comparative example and the above-mentioned Example 1 is that dopamine hydrochloride is not used to pretreat the glass fibers when preparing the graphene oxide-modified chopped glass fibers.
[0114] Performance testing
[0115] In order to better verify the mechanical properties and flame retardant properties of the composite materials obtained in the above embodiments and comparative examples, the composite materials obtained in the above embodiments 1-3 and comparative examples 1-5 are tested for various properties such as tensile strength, flexural strength, notched impact strength and vertical combustion performance (i.e. flame retardant performance), and the test results are as follows:
[0116]
[0117] It can be seen from the test data of the above embodiments 1-3 that the GF / PA composite material prepared by the method of the present invention not only maintains good mechanical properties, but also has excellent fire resistance. Specifically, the present invention adds graphene oxide modified glass fiber and halogen-free flame retardant to polyamide resin, and the active functional groups of graphene oxide grafted on the surface of glass fiber can interact with the polyamide resin matrix, thereby enhancing the interfacial bonding force between glass fiber and polyamide resin matrix, and then effectively improving the mechanical properties of glass fiber and polyamide resin composite matrix. At the same time, the unique lamellar structure of graphene oxide is evenly dispersed in the polyamide resin and superimposed layer by layer to form a dense physical barrier layer, blocking the flow of polyamide melt along the glass fiber, thereby eliminating the "candle wick effect" caused by GF when the GF / PA material burns, thereby avoiding the occurrence of aggravated fire. Therefore, the UL94 fire rating of the composite material can reach V-0 level.
[0118] From the test data of Example 1 and Comparative Example 1, it can be seen that the glass fiber has not been modified, and the "wick effect" caused by GF is obvious when the GF / PA composite material is burned, resulting in poor flame retardancy, which is only V-2 level. At the same time, its tensile strength, flexural strength and notched impact strength are respectively 12.0%, 7.9% and 17.2% lower than those of Example 1.
[0119] It can be seen from the test data of Example 1 and Comparative Example 2 that the amount of graphene oxide added cannot be too low when modifying the glass fiber. When the amount of graphene oxide added is too low, a complete coating cannot be formed on the surface of the glass fiber. Due to the uneven coating, the dispersion of graphene oxide on the polyamide resin is affected, resulting in poor flame retardancy. Therefore, the UL94 fire rating of Comparative Example 2 is only V-1. However, due to the active functional groups on the surface of graphene oxide, it can interact with the polyamide resin matrix, enhancing the interfacial bonding force between the glass fiber and the polyamide resin matrix. Therefore, its mechanical properties are still higher than those of Comparative Example 1.
[0120] It can be seen from the test data of Example 1 and Comparative Example 3 that the amount of graphene oxide added cannot be too high when modifying the glass fiber. If the amount of graphene oxide added is too high, self-polymerization will occur, causing uneven coating and agglomeration on the surface of the glass fiber. When the self-polymerization of graphene oxide is more serious, it will eventually affect the flame retardant properties of the GF / PA composite material. The UL94 fire rating of the GF / PA composite material obtained in Comparative Example 3 is only V-2, which is worse than the flame retardant effect of Comparative Example 2. However, due to the active functional groups on the surface of graphene oxide, it can interact with the polyamide resin matrix, thereby enhancing the interfacial bonding force between the glass fiber and the polyamide resin matrix. Therefore, its mechanical properties are still higher than those of Comparative Example 1.
[0121] It can be seen from the test data of Example 1 and Comparative Example 4 that the flame retardant properties of the GF / PA composite material will be seriously affected if nano-titanium dioxide is not added when the glass fiber is modified, so that its UL94 fire rating is only V-1. The possible reason is that nano-titanium dioxide and the like are deposited on the surface of graphene oxide during preparation, thereby preventing the aggregation of graphene oxide nanosheets and avoiding the self-polymerization of graphene oxide, so that graphene oxide can be well dispersed in the polyamide resin, thereby effectively eliminating the "candle wick effect" caused by GF when the GF / PA material burns. In addition, if nano-titanium dioxide is not added, the gap between the glass fiber and the polyamide resin cannot be well blocked, resulting in a weak combination of the glass fiber and the polyamide resin, so its mechanical properties are not as good as those of Example 1.
[0122] It can be seen from the test data of Example 1 and Comparative Example 5 that the graphene oxide cannot be treated with dopamine hydrochloride, so that the graphene oxide cannot be well adsorbed on the glass fiber, resulting in poor flame retardancy and mechanical properties, which are similar to the properties of unmodified glass fiber. Dopamine can form polydopamine in aqueous solution. This polydopamine has excellent adhesion properties and can be firmly adsorbed on solid surfaces. It is widely used in multifunctional surface coatings in different fields.
[0123] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0124] The above is a detailed introduction to the preparation method of a modified glass fiber reinforced polyamide composite material provided in the embodiments of the present application. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the technical solution and its core idea of the present application. Ordinary technicians in this field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some of the technical features therein with equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A modified glass fiber reinforced polyamide composite material, characterized in that: The raw materials include the following components by weight: Graphene oxide modified glass fiber: 10-40 parts by weight, Polyamide resin: 44-83 parts by weight, Flame retardant: 5-12 parts by weight, Lubricant: 0.2-0.5 parts by weight, Additives: 1-3 parts by weight.
2. The modified glass fiber reinforced polyamide composite material according to claim 1, characterized in that: The preparation method of the graphene oxide modified glass fiber comprises the following steps: S1, adding glass fiber to Tris-HCl buffer, and dispersing by ultrasonic for 15-25 minutes to obtain a mixed dispersion; wherein the addition ratio of the glass fiber to the Tris-HCl buffer is 10g:1000mL; the concentration of the Tris-HCl buffer is 0.01mol / L, and the pH is 8.5; S2, adding dopamine hydrochloride to the mixed dispersion and stirring continuously at room temperature for more than 18 hours, when the mixed dispersion changes from yellow-brown to black, the reaction is completed and the stirring is stopped, the mixed dispersion is centrifuged, and the centrifuged product is repeatedly washed with ethanol and deionized water to obtain polydopamine coated glass fiber; wherein the addition ratio of the dopamine hydrochloride to the glass fiber is 1g:10g; S3. Add polydopamine coated glass fiber, dopamine hydrochloride, nano titanium dioxide and graphene oxide in Tris-HCl buffer in sequence, and stir continuously at room temperature for more than 18 hours, then centrifuge, wash the centrifugal product repeatedly with ethanol and deionized water, and vacuum dry at 80°C to constant weight to obtain the graphene oxide modified glass fiber; wherein, in this step, the addition ratio of the Tris-HCl buffer, polydopamine coated glass fiber, dopamine hydrochloride, nano titanium dioxide and graphene oxide is 1000mL: 10g: 0.5g: 0.5g: 2g; the concentration of the Tris-HCl buffer is 0.01mol / L, and the pH is 8.
5.
3. The modified glass fiber reinforced polyamide composite material according to claim 1, characterized in that: The glass fiber is an alkali-free chopped glass fiber, the glass fiber diameter is ≤15 μm, and the chopped length of the glass fiber is ≤5 mm.
4. The modified glass fiber reinforced polyamide composite material according to claim 1, characterized in that: The polyamide resin is at least one of PA6, PA66, PA56, PA610, PA612, PA11, PA12, PA1010, and PA1012; and the relative viscosity of the polyamide resin is ≥2.0dl / g.
5. The modified glass fiber reinforced polyamide composite material according to claim 1, characterized in that: The flame retardant is a halogen-free flame retardant.
6. The modified glass fiber reinforced polyamide composite material according to claim 1, characterized in that: The flame retardant is at least one of red phosphorus flame retardant, diethyl aluminum phosphinate flame retardant, melamine polyphosphate and melamine cyanurate.
7. The modified glass fiber reinforced polyamide composite material according to claim 1, characterized in that: The lubricant is one of modified ethylene bis fatty acid amide, silicone masterbatch and montan wax, or a mixture of any two or more of them in any proportion.
8. The modified glass fiber reinforced polyamide composite material according to claim 7, characterized in that: The silicone masterbatch contains more than 50% ultra-high molecular weight siloxane, and the remaining carrier resin is LDPE or PA6; the montan wax is a mixture of OP wax and E wax; the addition ratio of OP wax to E wax in the mixture of OP wax and E wax is 2:
1.
9. The modified glass fiber reinforced polyamide composite material according to claim 1, characterized in that: The auxiliary agent is at least one of an antioxidant, a photoaging auxiliary agent, and a colorant.
10. A method for preparing a modified glass fiber reinforced polyamide composite material according to any one of claims 1 to 9, characterized in that: The steps include: The polyamide resin, flame retardant, lubricant and additives are mixed evenly and added to the main feeding port of the twin-screw extruder, and the graphene oxide modified glass fiber is added to the side feeding port of the twin-screw extruder according to the weight ratio. The composite material is obtained by melt blending, extruding and granulating through the twin-screw extruder.
Citation Information
Patent Citations
Preparation process of glass fiber composite material reinforced modified PET (Polyethylene Terephthalate) material
CN118165316A
Wear-resistant alcoholysis-resistant PP (polypropylene) reinforced material for replacing nylon glass fiber and preparation method of wear-resistant alcoholysis-resistant PP reinforced material
CN116535775A
Polyester foam material for automotive trim and preparation method of polyester foam material
CN118580648A
Flame-retardant high-temperature-resistant glass fiber reinforced nylon composite material and preparation method thereof
CN118599147A
Cited By
Multifunctional composite fiber reinforced decorative base paper and preparation method thereof
CN120989934A